Layered protein nanoparticles containing influenza B HA stalk induced sustained cross-protection against viruses spanning both viral lineages. (August 2022) - Song, Yufeng; Zhu, Wandi; Wang, Ye; Deng, Lei; Ma, Yao; Dong, Chunhong; Gonzalez, Gilbert X.; Kim, Joo; Wei, Lai; Kang, Sang-Moo; Wang, Bao-Zhong
Abstract: The influenza epidemics pose a significant threat to public health. Of them, type B influenza coincided with several severe flu outbreaks. The efficacy of the current seasonal flu vaccine is limited due to the antigenicity changes of circulating strains. In this study, we generated structure-stabilized HA stalk antigens from influenza B and fabricated double-layered protein nanoparticles as universal influenza B vaccine candidates. In vitro studies found that the resulting protein nanoparticles were effectively taken up to activate dendritic cells. Nanoparticle immunization induced broadly reactive immune responses conferring robust and sustained cross-immune protection against influenza B virus strains of both lineages. The results reveal the potential of layered protein nanoparticles incorporated with structure-stabilized constant antigens as a universal influenza vaccine with improved immune protective potency and breadth.